Muscle activity, cross-sectional area, and density following passive standing and whole body vibration: A case series. (September 2014) - Masani, Kei; Alizadeh-Meghrazi, Milad; Sayenko, Dimitry G.; Zariffa, Jose; Moore, Cameron; Giangregorio, Lora; Popovic, Milos R.; Catharine Craven, B.
Abstract : Objective: To investigate the effects of intermittent passive standing (PS) and whole body vibration (WBV) on the electromyography (EMG) activity, cross-sectional area, and density of lower extremity muscles in individuals with chronic motor complete spinal cord injury (SCI). Design: Case series. Methods: Seven adult men with chronic (≥2 years), thoracic motor complete (AIS A–B) SCI completed a 40-week course of thrice-weekly intermittent PS-WBV therapy, in a flexed knee posture (160°), for 45 minutes per session at a frequency of 45 Hz and 0.6–0.7 mm displacement using the WAVE ® Pro Plate, with an integrated EasyStand™ standing frame. EMG was measured in major lower extremity muscles to represent muscle activity during PS-WBV. The cross-sectional area and density of the calf muscles were measured using peripheral quantitative computed tomography at the widest calf cross-section (66% of the tibia length) at pre- and post-intervention. All measured variables were compared between the pre- and post-intervention measurements to assess change after the PS-WBV intervention. Results: PS-WBV acutely induced EMG activity in lower extremity muscles of SCI subjects. No significant changes in lower extremity EMG activity, muscle cross-sectional area, or density were observed following the 40-week intervention. Conclusions: Although acute exposure to PS-WBV can induce electrophysiological activity of lower extremity muscles during PS in men with motor complete SCI, the PS-WBV intervention for 40 weeks was not sufficient to result in enhanced muscle activity, or to increase calf muscle cross-sectional area or density.